Design, content, and fieldwork procedures of the COVID‐19 Psychological Research Consortium (C19PRC) Study – Wave 4. Issue 1 (5th November 2021) - McBride, Orla; Butter, Sarah; Murphy, Jamie; Shevlin, Mark; Hartman, Todd K.; Bennett, Kate M.; Stocks, Thomas V. A.; Lloyd, Alex; McKay, Ryan; Gibson‐Miller, Jilly; Levita, Liat; Mason, Liam; et al.
Abstract: Objectives: This paper outlines fieldwork procedures for Wave 4 of the COVID‐19 Psychological Research Consortium (C19PRC) Study in the UK during November–December 2020. Methods: Respondents provided data on socio‐political attitudes, beliefs, and behaviours, and mental health disorders (anxiety, depression, and posttraumatic stress). In Phase 1, adults ( N  = 2878) were reinvited to participate. At Phase 2, new recruitment: (i) replenished the longitudinal strand to account for attrition; and (ii) oversampled from the devolved UK nations to facilitate robust between‐country analyses for core study outcomes. Weights were calculated using a survey raking algorithm to ensure the longitudinal panel was representative of the baseline sample characteristics. Results: In Phase 1, 1796 adults were successfully recontacted and provided full interviews at Wave 4 (62.4% retention rate). In Phase 2, 292 new respondents were recruited to replenish the panel, as well as 1779 adults from Wales, Scotland, and Northern Ireland, who were representative of the socio‐political composition of the adult populations in these nations. The raking procedure successfully re‐balanced the longitudinal panel to within 1% of population estimates for selected socio‐demographic characteristics. Conclusion: The C19PRC Study offers a unique opportunity to facilitate and stimulate interdisciplinary research addressing important public health questions relating to the COVID‐19 pandemic.